G243(P) A Qualitative Study of the Barriers to the Pre-Hospital Management of Acute Pain in Children. (4th June 2013) - Murphy, A; Barrett, M; Cronin, J; McCoy, S; Larkin, P; Brenner, M; Wakai, A; O'Sullivan, R
Abstract : Aims: Effective pain management in the pre-hospital setting is gaining traction as a potential key performance indicator by many EMS systems, but historically has been shown to be inadequate, particularly in the paediatric population. This study aimed to identify the barriers, as perceived by a representative national cohort of Advanced Paramedics (APs), to achieving optimal prehospital management of acute pain in children. Methods: A qualitative approach was employed to capture data through two focus group interviews. 16 APs were invited to participate in this study. Both interviews were audio-recorded, transcribed, and analysed using Attridge-Stirling's framework for thematic network analysis. Ethical approval was granted for this study. Results: The global theme "Barriers to the Prehospital Management of Acute Pain in Children" emerged from three organising themes as follows: AP education and training, Current clinical practise guidelines for paediatric pain management, and Realities of prehospital practise. Limited exposure to children in the pre-hospital setting, difficulty assessing pain intensity in small children, and challenges in administering oral or inhaled analgesic agents to distressed and uncooperative children were highlighted by participants. Short transfer times to the ED and a "medical" cause of pain were also implicated as examples of when children are less likely to receive analgesia from practitioners. Conclusion: The pathway to improving care must be paved with an emphasis on improvements in practitioner education and training, offering alternatives to assessing pain in pre-verbal children, exploring the intranasal route of drug delivery in managing acute severe pain, and through robustly developing evidence-based guidelines that are practitioner friendly and patient-focused.